2012
DOI: 10.1074/jbc.m112.415984
|View full text |Cite
|
Sign up to set email alerts
|

Human Rap1 Interacts Directly with Telomeric DNA and Regulates TRF2 Localization at the Telomere

Abstract: Background: hTRF2 and hRap1 prevent non-homologous end joining and exist as a complex at human telomeres. Results: The TRF2-Rap1 complex has high specificity for telomeres and a higher affinity for 3Ј telomeric ends than hTRF2. Conclusion: hRap1 regulates the DNA binding characteristics of hTRF2. Significance: This is the first evidence of hRap1 interacting with DNA and altering the affinity of hTRF2 for telomeric DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 48 publications
8
63
3
Order By: Relevance
“…The observed selectivity increase is in a very good accordance with the results obtained recently from gel retardation assays by Arat and Griffith (18). Additionally, when we studied Rap1 effect on DNA binding of TRF2, we found that Rap1 induced TRF2 release from telomeric DNA duplexes.…”
Section: Discussionsupporting
confidence: 92%
“…The observed selectivity increase is in a very good accordance with the results obtained recently from gel retardation assays by Arat and Griffith (18). Additionally, when we studied Rap1 effect on DNA binding of TRF2, we found that Rap1 induced TRF2 release from telomeric DNA duplexes.…”
Section: Discussionsupporting
confidence: 92%
“…For example, overexpression of Trf2, which recruits hRap1 to DNA, can reduce nucleosome density within telomere chromatin, which suggests that the hRap1:Trf2 complex may modify chromatin (Galati et al 2012). Also, the recent demonstrations that mammalian Rap1 not only localizes to telomeres but also can bind with some affinity to DNA itself, contribute to the transcriptional regulation of sites throughout the genome, and bind several histone proteins raise the possibility that mammalian Rap1 may contribute to changes in chromatin and gene expression in senescent cells (Martinez et al 2010;Lee et al 2011;Yang et al 2011;Arat and Griffith 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy analysis of t-loop formation has revealed that the Rap1–TRF2 complex, compared to TRF2 alone, is much more prone to bind telomeric DNA and to form t loops 18 . Rap1 binding to TRF2 also decreases electrostatic interactions between double-stranded DNA and the TRF2 basic domain, thereby decreasing nonspecific binding of TRF2 to DNA and increasing the specificity of TRF2 for telomeric DNA 19 .…”
Section: The End Protection Problem: Inhibition Of the Ddrmentioning
confidence: 99%
“…Steps of DNA damage–repair inhibition by shelterin or accessory factors are highlighted by red circles. (1) TRF2, potentially through its TRFH domain, and supported by Rap1, forms the t loop, a DNA structure that hides chromosome ends from the MRN–ATM factors 79,18 . (2) The t loop also prevents loading of the Ku heterodimer on chromosome ends.…”
Section: Figurementioning
confidence: 99%